Análise da transmissão assimétrica de preços no mercado de leite em Goiás de 2005 a 2013 - Carvalhaes, Gracielle Couto (2014)
Considering the importance of the State of Goias in the national dairy market and the rise of Brazil on the world stage production of milk , this study started from the analysis of the milk market in Goias considering the stages of production , processing and marketing , in order to analyze the behavior agents of the milk production chain in Goias (producer , wholesale and retail ) in order to verify that the price adjustment is asymmetric in that supply chain , as well as , the variations in increases in prices are transmitted with greater speed and a greater magnitude than the decrease . Thus, for conducting this study, it was necessary to use theoretical models that could support the use of econometric models , these in turn helped in quantifying the impacts caused prices will change , in order to support the specific objective of the work , which sought to examine the relationship between the prices of milk production chain by estimating models and calculating sales margins . Overall the results indicate that the adjustment of prices to market milk in Goias is asymmetric, being attacked the main agent responsible for this failure.